Indications for the use of Dobutamine in the Cardiology Ward and Emergency Room of a Public Hospital in the Federal District (Global Journal of Medical Research, 2023)
Dobutamine is an inotropic drug used in the treatment of decompensated heart failure and septic and cardiogenic shock It is a sympathomimetic amine that stimulates beta-1 and beta-2 adrenoceptors leading to the inotropic effect Acting on stroke volume and cardiac output in a directly proportional manner it slightly increases blood pressure and heart rate and reduces peripheral vascular resistance The main clinical indication of Dobutamine occurs through the findings of tissue hypoperfusion on physical examination presented by slow capillary refill cold skin thin pulse and or tachycardia To evaluate the main indications for the use of dobutamine in patients in a cardiology ward and emergency room of a public hospital in the Federal District a retrospective study was carried out based on the analysis of 80 medical records of patients using the TRAK CARE version 2015 system SES DF data system admitted to the cardiology ward and emergency room cardiology units of the Regional Hospital of Taguatinga between December 2020 and July 2021
Keywords: dobutamine heart failure cardiology